FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PROFESI GURU MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN (S1) JURUSAN TEKNIK SIPIL FT UNP - 957-976 , Arif Firman Alim (Universitas Negeri Padang, 2016)
ABSTRAK The study program of Technical Education Building Department of Civil Engineering, Faculty of Engineering, Padang State University is a program of study that prepares students to become professional workers in the field of vocational education. Graduates of Technical Education Building Program can be expected natinya prospective teachers Vocational High School of Technology and Engineering Education Building Techniques. Based on the interviews and the results of previous studies it is known that students are not interested in the teaching profession. To determine the factors that affect the interests of the teaching profession, the authors conducted a study with the title: Factors Affecting Student Interests Professional Teacher Education Program Building Engineering Department of Civil Engineering Faculty of Engineering, Padang State University. This research is descriptive. The study population is students of Technical Education Building Department of Civil Engineering, Faculty of Engineering, Padang State University year in 2014. The sampling technique used total sampling method with a total sample of 68 respondents. The instrument used for data collection was a questionnaire study. Data analysis technique used is descriptive statistical analysis techniques with percentage calculations. The results of this research, there are five sub-indicators of internal factors that affect the interests of the teaching profession that is emotional, perception, motivation, talent and mastery of science. Of the five sub-indicators of the talent factor is the internal factors that most influence. Factors influential talents of 25.41% interest in the teaching profession to students of Technical Education Building Department of Civil Engineering Faculty of Engineering, Padang State University year in 2014. Keywords: internal factors, interest, teaching profession